Multidimensional evalutation of young handball players: Discriminant analysis applied to talent selection - Vila, H.; Rodriguez, F.; Fernandez, J.; Ferragut, C. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The aim of this study was to analyse different anthropometrical, physical fitness and training characteristics of young female handball players of different age categories from a multidimensional perspective. The predictive capacity of multivariate models developed by discriminant analysis reached around of 90% of players correctly classified when all variables were included.